Extremely red quasars from SDSS, BOSS and WISE: classification of optical spectra. Issue 4 (14th September 2015) - Ross, Nicholas P.; Hamann, Fred; Zakamska, Nadia L.; Richards, Gordon T.; Villforth, Carolin; Strauss, Michael A.; Greene, Jenny E.; Alexandroff, Rachael; Brandt, W. Niel; Liu, Guilin; Myers, Adam D.; Pâris, Isabelle; et al.
Abstract: Quasars with extremely red infrared-to-optical colours are an interesting population that can test ideas about quasar evolution as well as orientation, obscuration and geometric effects in the so-called AGN unified model. To identify such a population, we match the quasar catalogues of the Sloan Digital Sky Survey (SDSS), the Baryon Oscillation Spectroscopic Survey (BOSS) to the Wide-Field Infrared Survey Explorer ( WISE ) to identify quasars with extremely high infrared-to-optical ratios. We identify 65 objects with r AB − W 4Vega > 14 mag (i.e. F ν (22 μm)/ F ν ( r ) ≳ 1000). This sample spans a redshift range of 0.28 < z < 4.36 and has a bimodal distribution, with peaks at z ∼ 0.8 and z ∼ 2.5. It includes three z > 2.6 objects that are detected in the W 4 band but not W 1 or W 2 (i.e. ' W 1 W 2 dropouts'). The SDSS/BOSS spectra show that the majority of the objects are reddened type 1 quasars, type 2 quasars (both at low and high redshift) or objects with deep low-ionization broad absorption lines (BALs) that suppress the observed r -band flux. In addition, we identify a class of type 1 permitted broad emission-line objects at z ≃ 2–3 which are characterized by emission line rest-frame equivalent widths (REWs) of ≳150 Å, much larger than those of typical quasars. In particular, 55 per cent (45 per cent) of the non-BAL type 1s with measurable C iv in our sample have REW(C iv ) > 100 (150) Å, compared to only 5.8 per cent (1.3 per cent) for non-BAL quasars in BOSS. These objects often also have unusual line ratios, such as very high N v /Ly α ratios. These large REWs might be caused by suppressed continuum emission analogous to type 2 quasars; however, there is no obvious mechanism in standard unified models to suppress the continuum without also obscuring the broad emission lines.